Letter from James Curtis Booth to W. W. Montgomery, August 13, 1880 - Booth, James Curtis (1880)
James Curtis Booth (1810-1888) writes to W. W. Montgomery to complain of Mr. F. Sylvester's unavailability regarding the sale of a property.
Keywords: Booth, James Curtis, 1810-1888; Real property; Montgomery, W. W.; Sylvester, F.